Solar homogeneous catalysis to the removal of organic matter from slaughterhouse effluents undergone to a prior biological process - J. A. Hurtado (IWA Publishing, 2021)
This study shows the effectiveness of the wastewater treatment from a municipal slaughterhouse that has undergone a previous biological treatment applying a sequence of stages, reaching a 75% of elimination of the chemical oxygen demand (COD) using sedimentation in combination with coagulation–flocculation, using 0.5 g/L FeCl3 which is one of the best known inorganic coagulants. Then, the elimination of COD was around 98% adding the Fenton process in which 1,000 mg/L H2O2 and FeSO4 were used. In addition to the COD, other water quality parameters were measured to evaluate the level of purification of the test samples, such as solids of different types, pH, DOC and so on. With the above process, it can be noted that the Fenton process produced a slight improvement in the effluent quality by using a solar concentrator in the now-called photo-Fenton process, reaching around 99% of COD removal (0.36 g/L), 91% of total suspended solids (0.32 g/L) and 89% of dissolved organic carbon (0.20 g/L). These results were the best achieved within a proposed treatment train for this type of complex wastewater. Moreover, this last part of the process adds an improvement by the usage of renewable energy sources such as sunlight. HIGHLIGHT This article deals with work on real wastewater treatment under real working conditions, such as the use of sunlight. In addition, a parabolic solar concentrator built from reused material was used. So the project has elements of sustainability.;